2020
DOI: 10.31878/ijcbr.2020.62.08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Anthropometric Parameters and Intelligence in Preschool Children From Rural Konkan

Abstract: Aim: To study association between anthropometric parameters and intelligence in preschool children from Rural KONKAN.Method: Children between 3 to7 years of age were examined for anthropometry, dietary recall and Intelligence (Intelligent Quotient-IQ) assessment from rural anganwadis. IQ test was performed by clinical psychologist using Binet-Kamat test of intelligence (version 4). Nutritional information was collected from 24- hour dietary recall and food diversity. Results: Results were interpreted using Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…It is important to note that most of the studies that report an association between anthropometric measures and cognitive function also highlight the confounding influence of SES. Our study lacks a thorough examination of socioeconomic factors, but our conclusions are consistent with Patil et al who failed to detect any significant correlation between anthropometric measures and IQ (Patil et al, 2020). Nonethe-less, it is crucial to acknowledge that SES could have influenced the outcomes of our investigation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is important to note that most of the studies that report an association between anthropometric measures and cognitive function also highlight the confounding influence of SES. Our study lacks a thorough examination of socioeconomic factors, but our conclusions are consistent with Patil et al who failed to detect any significant correlation between anthropometric measures and IQ (Patil et al, 2020). Nonethe-less, it is crucial to acknowledge that SES could have influenced the outcomes of our investigation.…”
Section: Discussionsupporting
confidence: 88%
“…They found inconsistent results and suggested that the most accurate predictors of certain cognitive capacities, particularly vocabulary abilities, affective labelling, and IQ composite, were BMI and androstenedione (Azurmendi et al, 2005). On the other hand, Patil et al assessed anthropometry, dietary recall, and intelligence (Intelligent Quotient-IQ) in 3 to 7 year old children from rural Anganwadis in India and reported that despite high prevalence of malnutrition, there was no correlation between anthropometry and IQ (Patil et al, 2020). Several studies showed a lack of correspondence between IQ and various anthropometric measures in preschool-aged children.…”
Section: Introductionmentioning
confidence: 99%